Sacred planet : with Gulnaz Khan [videorecording (DVD)] - Khan, Gulnaz (PBS, 2025)
Examine the impact of climate change on sacred places around the world with journalist Gulnaz Khan. Meet faith leaders drawing on ancient wisdom and spiritual resilience to confront the crisis with hope and action in this powerful four-part series.